2018
DOI: 10.1016/j.sleep.2017.11.1121
|View full text |Cite
|
Sign up to set email alerts
|

Elevated tau and interleukin-6 concentrations in adults with obstructive sleep apnea

Abstract: Obstructive sleep apnea (OSA) is characterized by apneas and hypopneas that result in hypoxia, cerebral hypoperfusion, endothelial dysfunction, inflammation, and oxidative stress. These pathophysiologic processes likely contribute to neuronal damage. Tau is a protein that stabilizes microtubules and, along with amyloid beta (Aβ), is associated with neurodegenerative processes. We sought to determine if tau and other biomarkers of inflammation were related to OSA severity. Concentrations of tau, Aβ40, Aβ42, c-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 46 publications
2
51
1
Order By: Relevance
“…24 Previously conducted cross-sectional, casecontrol, prospective cohort studies as well as randomized controlled trials provided evidence for a positive association between sleep behaviors and inflammatory mediators such as CRP, IL-6, IL-8, TNF-, and von Willebrand factor antigen. 20,32,35,37,40,41,47 However, these studies were heterogeneous with respect to target population as well as definition of sleep behavior, with the majority focused on OSA. We found that hours of sleep were not related to WBC markers, after controlling for sociodemographics, lifestyle, and health characteristics, including periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Previously conducted cross-sectional, casecontrol, prospective cohort studies as well as randomized controlled trials provided evidence for a positive association between sleep behaviors and inflammatory mediators such as CRP, IL-6, IL-8, TNF-, and von Willebrand factor antigen. 20,32,35,37,40,41,47 However, these studies were heterogeneous with respect to target population as well as definition of sleep behavior, with the majority focused on OSA. We found that hours of sleep were not related to WBC markers, after controlling for sociodemographics, lifestyle, and health characteristics, including periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…A priori confounders for the hypothesized relationships were identified based on the existing literature 16,20,25,26,28,29,[31][32][33][34][35][36][37][38][39][40][41] and classified as sociodemographic, lifestyle, and healthrelated characteristics. Sociodemographic characteristics included age (in years; 30 to 34, 35 to 39, 40 to 44, 45 to 49, 50 to 54, 55 to 59, 60 to 64, 65 to 96, and ≥70), race (Mexican American, other Hispanic, non-Hispanic white, non-Hispanic black, and other), education (<high school, 9th to 11th grade, high school graduate/GED or equivalent, some college or AA degree, college graduate or higher), marital status (married/living with partner, other) and poverty income ratio (<100%, 100% to <200%, and ≥200%).…”
Section: Covariatesmentioning
confidence: 99%
“…Sleep disturbances have also been linked to increased symptom reporting and have been shown to hinder recovery following TBI (White et al., ). Finally, there is converging evidence that sleep affects protein concentrations in the central nervous system, including in terms of alterations in levels of both tau and Aβ (Ju et al., ; Motamedi et al., ). Sleep is the clearance mechanism for the glymphatic system, ridding the brain of excess proteins, including tau (Iliff et al., ; Louveau et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In young adults, whereas OSA was not associated with blood Aβ 42 and Aβ 40 levels, moderatesevere OSA was associated with increased blood total tau levels compared to both mild OSA and controls [70]. In another study, middle-aged OSA subjects had significantly higher blood Aβ 40 and Aβ 42 levels as well as phosphorylated tau levels compared to controls, although unchanged total tau levels were observed [71].…”
Section: Blood-based Biomarkers Of Ad Neuropathology In Osamentioning
confidence: 91%